The Substitute Notary's Responsibility for Errors in the Deed He/She Made - Huda, Indra Kusuma; Hafidz, Jawade (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to analyze: 1) The duties and authorities of a Substitute Notary. 2) The responsibilities of a Substitute Notary if there is an error in the making of the deed he made. The approach method used in this study is an empirical juridical approach. The type of data uses primary data and secondary data obtained through interviews and literature studies. The data analysis method used in this study is qualitative descriptive analysis. The results of the study concluded: 1) The duties and authorities of a Substitute Notary are that a substitute Notary has the same duties and authorities as the replaced Notary or the Appointing Notary. Article 2 Paragraph 1 of Law Number 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary, which states that a Notary is a public official who is authorized to make authentic deeds and has other authorities as referred to in this Law or based on other laws. The authority that exists in a Notary does not come from other government institutions, but rather the authority that is based on and granted by the Law. 2) The responsibility of the Substitute Notary if there is an error in making the deed he made is the same as the notary he appointed. Notary Abdul Moethalib Wahab above is an individual responsibility, the notary's actions are proven to have committed the crime of forgery of documents. Criminal responsibility for notaries is regulated in the Criminal Code, if the notary commits the crime of forgery of documents, as referred to in the criminal provisions regulated in Article 263 paragraph (1) and Article 264 paragraph (1) of the Criminal Code. Notaries who are proven guilty of a crime and have permanent legal force cannot be immediately dismissed dishonorably by the Minister of Law and Human Rights due to the uncertainty in the regulations of the Law on the Position of Notary, as contained in Articles 12 and 13 of the Law on the Position of Notary. Keywords: Criminal; Responsibility; Substitute Notary.